Exploring The Use of Storytelling Technique in Speaking Activities for Junior High School Students - Hanifah, Fadia; Ahmad, Yousef Bani (PROJECT (Professional Journal of English Education), 2026)
The purpose of this study is to explore storytelling as a learning technique to support speaking practice among junior high school students and to describe their perceptions of the activity. While many studies focus on storytelling’s effect on speaking performance, fewer address how students experience it. This study was conducted at SMPN 2 Telukjambe Timur, Karawang, with one eighth-grade class, using a qualitative case study design. Data were gathered through classroom observation, semi-structured interviews, and documentation, then analyzed thematically. Findings reveal that storytelling offers students opportunities to speak more fluently, construct sentences carefully, and use clearer pronunciation. Students also reported that preparing and presenting stories encouraged them to practice new vocabulary and apply narrative structures during oral tasks. Beyond language development, storytelling was perceived as enjoyable and motivating, inspiring practice inside and outside the classroom. Despite challenges such as nervousness, hesitation, and forgetting parts of the story, students developed strategies to cope and gradually became more confident speaking before peers. These results show that storytelling is not only a language task but also a supportive approach that fosters motivation, confidence, and participation.